Homebased rehabilitation: Physiotherapy student and client perspectives - Dianne Parris; Susan van Schalkwyk; Dawn Ernstzen (South African Medical Association, 2016)
Background. Home-based rehabilitation (HBR) in under-resourced areas in a primary healthcare (PHC) context exposes students to the real-life situations of their clients. There is a scarcity of literature on student and client experiences of HBR in the physiotherapy context. Increased knowledge of HBR could result in an enhanced experience for both student and client. This study sought to discover the perceptions of final-year physiotherapy students and their clients relating to their experiences of HBR during a PHC placement in a resource-constrained setting. Objectives. To explore the experiences and perceptions of physiotherapy students and their clients regarding HBR as part of clinical training in resource-constrained settings. To discover the barriers to and facilitators of effective HBR. Methods. An exploratory case study was performed. A qualitative phenomenological research design in the interpretivist paradigm was used. Semistructured interviews were conducted with clients (n=7) living in an under-resourced setting, who had received HBR from physiotherapy students. Paired interviews were conducted with final-year physiotherapy students (n=6) after their HBR placement. Results. Clients appreciated the students’ services; however, data revealed communication barriers and unmet expectations. Students reported struggling to adapt to the context, resulting in interventions not being sufficiently client-centred. They voiced a need for language competency and earlier exposure to such contexts. Conclusion. Exposure to real-life situations in under-resourced settings in HBR provides valuable situated and authentic learning opportunities for physiotherapy students. The experience can be useful in preparing graduates to address the needs of the populations they serve during community service.